Smart Gardening Berbasis IoT Menggunakan Pengendali Mikro ESP32 Serta Protokol Komunikasi Modbus - Yani Prabowo; Tatang Wirawan Wisnuadji; Yan Everhard; Daffa Putra (CV. Multi Kreasi Media, 2023)
The internet has now become part of human life both in villages and cities, as long as it is still accessible by cellular communication networks, the internet will be easily accessible, by anyone as long as they have a device, this internet will hereinafter be called the Internet of Things (IoT), this internet in addition to providing Various information can also be used for control systems or control systems. To utilize the Internet, you need a device that has access to the internet network, the ESP32 microcontroller is one of the microcontrollers that can be used to access the internet, with this microcontroller it can also be used as a controller which can receive data from the environment and then process the data according to the embedded program. . It is possible that the microcontroller can be applied in plantations, how to create a minimum system design based on an ESP32 microcontroller with communication capabilities via the internet to be applied in plantations. The method in this research is the design and minimum design of a microcontroller-based system and how to integrate between microcontroller-based IoT devices and how SCADA protocols and technology can be implemented as a reliable system.